Dynamics of Motivation, Learning Experience, and Academic Challenges of International Students at State Islamic Religious Universities in Indonesia - Arif Zamhari; Hesti Kusumaningrum; Putra Setya, Rakha; Azahra, Salsabila; Sulfa Mani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
The increased mobility of international students demands a deep understanding of their motivations, learning experiences, and academic challenges. This study explores the factors that influence the selection of Indonesia as a study destination as well as the process of academic, social, cultural, and psychological adaptation of students at State Islamic Religious Universities (PTKIN), as well as providing insights for the development of international academic policies and practices. A phenomenological qualitative approach was used through in-depth interviews and focused group discussions (FGDs) with international students from various PTKINs, including UIN Malang, UIN Jakarta, and UIN Yogyakarta. The analysis emphasizes students' subjective experiences related to motivation, learning, and academic barriers. The results of the study showed that students' motivation was influenced by intrinsic and extrinsic factors, including religious interests, cultural interests, family support, scholarships, career prospects, language skills, and the desire to deepen religious knowledge. Learning experiences include social, cultural, academic, and psychological adaptation, influenced by language skills, peer support, organizational involvement, inclusive teaching methods, and institutional services such as the Indonesian Language for Foreign Speakers (BIPA) program and International Office assistance. The variety of services between PTKIN can be seen, for example, UIN Malang excels in personal mentoring, UIN Jakarta in program flexibility and BIPA, and UIN Yogyakarta in academic access and administrative support. The main academic challenges include language barriers, academic literacy, information limitations, study pressure, curriculum adjustments, and lack of multilingual references and psychosocial support. These findings provide important implications for PTKIN in improving academic services, supporting the adaptation of international students, and strengthening campus internationalization.